Focus on the Contribution of Oxidative Stress in Skin Aging - Federica Papaccio; Andrea D'Arino; Silvia Caputo; Barbara Bellei (MDPI AG, 2022)
Skin aging is one of the most evident signs of human aging. Modification of the skin during the life span is characterized by fine lines and wrinkling, loss of elasticity and volume, laxity, rough-textured appearance, and pallor. In contrast, photoaged skin is associated with uneven pigmentation (age spot) and is markedly wrinkled. At the cellular and molecular level, it consists of multiple interconnected processes based on biochemical reactions, genetic programs, and occurrence of external stimulation. The principal cellular perturbation in the skin driving senescence is the alteration of oxidative balance. In chronological aging, reactive oxygen species (ROS) are produced mainly through cellular oxidative metabolism during adenosine triphosphate (ATP) generation from glucose and mitochondrial dysfunction, whereas in extrinsic aging, loss of redox equilibrium is caused by environmental factors, such as ultraviolet radiation, pollution, cigarette smoking, and inadequate nutrition. During the aging process, oxidative stress is attributed to both augmented ROS production and reduced levels of enzymatic and non-enzymatic protectors. Apart from the evident appearance of structural change, throughout aging, the skin gradually loses its natural functional characteristics and regenerative potential. With aging, the skin immune system also undergoes functional senescence manifested as a reduced ability to counteract infections and augmented frequency of autoimmune and neoplastic diseases. This review proposes an update on the role of oxidative stress in the appearance of the clinical manifestation of skin aging, as well as of the molecular mechanisms that underline this natural phenomenon sometimes accelerated by external factors.